Fortaleciendo la transparencia y la ética en la contabilidad pública: desafíos y perspectivas en América Latina - Morocho Marin, Janeth Paola (2024)
The modernization of public accounting in Latin America is conclusive in a globalized context and economic crisis. This study analyzes the need to adapt to a competitive environment, highlighting the International Public Sector Accounting Standards as essential tools to improve government management. It focuses on professional ethics and transparency in the management of public resources, citing examples of legislation and practices in Latin America. The objective is to address ethical challenges in government accounting through a comprehensive approach that includes the promotion of ethical practices, training in values, strategic use of technology and active citizen participation. The research concludes that these measures will strengthen transparency and integrity in the management of public resources in Latin America, promoting a solid and sustainable ethical culture in the public sector.